ENCUESTA DE OPINIÓN PÚBLICA COMO DESIDEOLOGIZADOR - Martin Baró, Ignacio (La Sociología en sus Escenarios, 2009)
Abstract. A civil war poses problems that social scientists are calling for immediate solution, but also other, less urgent, though perhaps more basic. Among these is the ideological concealment of reality to the people, power that their alienation by separating their daily experience for its objectification, her experiential awareness of its necessary formalization. The systematic use of dialectical and public opinion polls to help dismantle the lie of the official discourse and open the collective consciousness to new historical alternatives. The proposal is discussed in the light of surveys carried out in the middle of the Salvadoran civil war, which show the disagreement between public discourse and the real opinion on topics as serious as the American intervention, the role of elections and the option for a dialogue Peace between the government and insurgents. Resumen. Una guerra civil plantea a los científicos sociales problemas que reclaman una solución inmediata, pero también otros, menos urgentes, aunque quizá más básicos. Entre estos se encuentra el ocultamiento ideologizado de la realidad a la población, que potencia su alienación al separar su vivencia cotidiana de su correspondiente objetivación, su conciencia experiencial de su necesaria formalización. El uso sistemático y dialéctico de las encuestas de opinión pública para ayudar a desmontar la mentira del discurso oficial y a abrir la conciencia colectiva a nuevas alternativas históricas. La propuesta se examina a la luz de encuestas desarrolladas en medio de la guerra civil salvadoreña, que muestran el desacuerdo entre el discurso público y la opinión real sobre temas tan graves como la intervención norteamericana, el papel de las elecciones y la opción por un diálogo de paz entre gobierno e insurgentes.